2010
DOI: 10.1371/journal.pone.0012253
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Campylobacter jejuni Strain M1

Abstract: Campylobacter jejuni strain M1 (laboratory designation 99/308) is a rarely documented case of direct transmission of C. jejuni from chicken to a person, resulting in enteritis. We have sequenced the genome of C. jejuni strain M1, and compared this to 12 other C. jejuni sequenced genomes currently publicly available. Compared to these, M1 is closest to strain 81116. Based on the 13 genome sequences, we have identified the C. jejuni pan-genome, as well as the core genome, the auxiliary genes, and genes unique be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
95
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 75 publications
(81 reference statements)
6
95
1
1
Order By: Relevance
“…For example, sequences from 18 (28%) of the isolates clustered in a large clade with C. jejuni M1 (Fig. 1B), a strain transmitted from poultry to humans that is associated with human gastroenteritis (32). Also in that large clade was C. jejuni ICDCCJ07001, isolated from a human with GuillainBarré syndrome in Jilin, China (33) (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, sequences from 18 (28%) of the isolates clustered in a large clade with C. jejuni M1 (Fig. 1B), a strain transmitted from poultry to humans that is associated with human gastroenteritis (32). Also in that large clade was C. jejuni ICDCCJ07001, isolated from a human with GuillainBarré syndrome in Jilin, China (33) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…1A [C. coli clade]). None of the Campylobacter isolates from crows grouped in a clade with C. avium, a species recently found in poultry that is divergent from C. jejuni (32).…”
Section: Prevalencementioning
confidence: 90%
“…When Friis and colleagues examined the genome of C. jejuni M1, they found a number of the genes, which have previously been described as being related to chicken colonization, to be present in this strain (21). These included genes such as cadF, which encodes the Campylobacter adhesion to fibronectin protein (28,29), and flpA, which has been shown to be important in chicken colonization (30).…”
Section: Figmentioning
confidence: 99%
“…C. jejuni isolates from these birds have been implicated in human disease (11,16,17). Other studies indicate that some Campylobacter isolates found in wild birds may not be pathogenic to humans (14,(18)(19)(20)(21)(22)(23). These conflicting reports indicate that studies using higher resolution molecular methods …”
mentioning
confidence: 99%
“…To date, however, the application of taxonomically conserved housekeeping genes, while phylogenetically useful, does not include biologically informative genes, such as virulence factors (29), thereby limiting conclusions about potential pathogenicity. Recent studies have demonstrated the importance of whole-genome sequencing (WGS) in understanding C. jejuni pathogenicity and transmission (18,21,23,30); however, to date, studies of Campylobacter in wild birds have not taken advantage of WGS approaches to define the genotypes that are associated with zoonotic transmission and virulence.…”
mentioning
confidence: 99%